Bureaucracy and Corruption in Public Sector Accounting - IONESCU, Luminiţa; CALOIAN, Florentin (Annals of Spiru Haret University. Economic Series, 2014)
Bureaucracy and corruption represent major causes of fiscal crises, and structural unemployment all over the world. According to WEF 2014 Global Risk Report, the bureaucracy has a high level in European countries and appreciation is growing that high historical rates of economic progress, especially those experienced by emerging markets, may not be sustainable in the future. Corruption is growing in a changing global environment and is considered one of the most important geopolitical risks. Most of the time, corruption is associated with fraud and money laundering. European growing cities and public administration have a strong influence over bureaucracy in public sector accounting and more time to process the accounting and fiscal information.